2017
DOI: 10.3389/fmicb.2017.01495
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Allelochemicals But Not Cyanobacterial Cells Markedly Reduce Microbial Community Diversity

Abstract: The freshwater cyanobacterium Phormidium sp. LEGE 05292 produces allelochemicals, including the cyclic depsipeptides portoamides, that influence the growth of heterotrophic bacteria, cyanobacteria, and eukaryotic algae. Using 16S rRNA gene amplicon metagenomics, we show here that, under laboratory conditions, the mixture of metabolites exuded by Phormidium sp. LEGE 05292 markedly reduces the diversity of a natural planktonic microbial community. Exposure of the same community to the portoamides alone resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Another hypothesis might be related to the effect of competition/exclusion mechanisms on community composition (Aguilera et al, 2017a;Dokulil and Teubner, 2000;Litchman, 2003). For instance, Cyanobacteria are more efficient than other groups for light-harvesting in low-light conditions generated by high biomass (Litchman, 2003;Schwaderer et al, 2011) and are able to release a wide variety of allelochemical compounds (Dias et al, 2017;Holland and Kinnear, 2013;Leflaive and Ten-Hage, 2007). To conclude, it ap pears that the ecological particularities of this group allow their dominance in waterbodies under anthropogenic pressure, and this resulted in enhanced community functioning through selection effect.…”
Section: Relationships Between Phytoplankton Communities Structure Fmentioning
confidence: 99%
“…Another hypothesis might be related to the effect of competition/exclusion mechanisms on community composition (Aguilera et al, 2017a;Dokulil and Teubner, 2000;Litchman, 2003). For instance, Cyanobacteria are more efficient than other groups for light-harvesting in low-light conditions generated by high biomass (Litchman, 2003;Schwaderer et al, 2011) and are able to release a wide variety of allelochemical compounds (Dias et al, 2017;Holland and Kinnear, 2013;Leflaive and Ten-Hage, 2007). To conclude, it ap pears that the ecological particularities of this group allow their dominance in waterbodies under anthropogenic pressure, and this resulted in enhanced community functioning through selection effect.…”
Section: Relationships Between Phytoplankton Communities Structure Fmentioning
confidence: 99%
“…However, in this study, the greatest allelopathic effect was observed for picocyanobacterium growing in a nutrient‐sufficient culture medium. Other authors also observed that some cyanobacteria can cause allelopathy under non‐limiting nutrient conditions (Allen et al, ; Bittencourt‐Oliveira et al, ; Brutemark et al, ; Dias et al, ; Leflaive & Ten‐Hage, ). Allen et al () showed that allelopathic compounds produced by green algae Uronema confervicolum were the highest in the treatment with the highest nutrient level and were much lower in the unbalanced nutrients treatments.…”
Section: Discussionmentioning
confidence: 92%
“…It has been also proposed that changes in the plankton community structure are caused by the differential effect of allelochemicals on different species (Mulderij, Van Donk, & Roelofs, 2003). Target organisms may be completely eliminated, inhibited, resistant to the allelochemicals, or be stimulated (e.g., Barreiro et al, 2017;Brutemark, Vandelannoote, Engström-Öst, & Suikkanen, 2015;Dias et al, 2017;Pichierri et al, 2017;Śliwińska-Wilczewska et al, 2017). However, as picocyanobacterial allelopathy is a relatively new topic of research in aquatic ecosystems, fewer studies, and information exist (Barreiro Felpeto, Śliwińska-Wilczewska, Złoch, & Vasconcelos, 2018;Costa et al, 2015;Śliwińska-Wilczewska et al, 2017;Śliwińska-Wilczewska, Pniewski, & Latała, 2016).…”
mentioning
confidence: 99%
“…The antibacterial activity of two Ludwigia species (invasive aquatic weeds) against a series of bacteria, including pathogens, has been demonstrated [58]. The production of antibiotics as allelochemicals by phytoplankton and cyanobacteria has also been documented [59][60][61][62][63]. However, antibiotic-induced interactions among marine microorganisms have mostly been highlighted within marine biofilms [64].…”
Section: Selection Of Drug-resistant Microorganism Can Occur In Surfamentioning
confidence: 99%